Pupil – a refugee in the Czech education system: a case study - Martina Kurowski (Sociální Pedagogika, 2013)
The article deals the topic of the education of migrants, specifically to a pupil who, along with his family, received asylum in the Czech Republic. The first part of the study is devoted to introducing the issue of the education of pupils with refugee backgrounds. We deal with the question of who is a refugee student and we also try to briefly describe the educational theories, from which the topic may be inspired. The largest part of the text is devoted to the analysis of a case study in which we try to see the issue through the eyes of the three stakeholders: the mother of the pupil, the teacher of the pupil and the pupil himself. The study analyses qualitative processed semi-structured interviews. As a research design we chose a case study because we are convicted it is the right way to get deeper into the issue, which is of interest to our country and the world.